Klasifikasi Jenis Beras Menggunakan Deep Learning Berbasis Computer Vision dengan Platform Roboflow - Imron Hefni F; Muhamad Soleh Sulaeman; Tri Herdiawan Apandi; Willy Muhammad Fauzi (Fakultas Ilmu Komputer, 2026)
Rice is a fundamental food commodity globally, where accurate variety classification is crucial for pricing, quality control, and food security. Manual classification methods are labor-intensive, time-consuming, and prone to human subjectivity. This research proposes an automated classification system for five rice varieties (Arborio, Basmati, Ipsala, Jasmine, and Karacadag) using a Computer Vision approach with Vision Transformer (ViT) architecture. Unlike Convolutional Neural Networks (CNN) which focus on local features, ViT utilizes selfattention mechanisms to capture global contextual relationships within images. The model was developed using the public